Molecular characteristic and pathogenicity of Indonesian H5N1 clade 2.3.2 viruses - NLPI, Dharmayanti; R, Hartawan; DA, Hewajuli; ., Hardiman; H, Wibawa; ., Pudjiatmoko (Indonesian Journal of Animal and Veterinary Sciences, 2013)
The outbreak of disease in late 2012 in Indonesia caused high duck mortality. The agent of the disease was identified as H5N1 clade 2.3.2. The disease caused economic loss to the Indonesian duck farmer. The clade 2.3.2 of H5N1 virus has not previously been identified, so this study was conducted to characterize 4 of H5N1 clade 2.3.2 viruses by DNA sequencing in eight genes segment virus namely HA, NA, NS, M, PB1, PB2, PA and NP.Â  The pathogenicity test of clade 2.3.2 viruses in ducks was compared to clade 2.1.3 viruses which predominat circulating in Indonesia. Results of phylogenetic tree analysis showed that the four of clade 2.3.2 viruses isolated in 2012 was the new introduced virus from abroad. Further analysis showed eight genes were in one group with the clade 2.3.2 viruses, especially those from VietNam and did not belong to Indonesia viruses group. The pathogenicity test in ducks showed that virus H5N1 clade 2.3.2 and clade 2.1.3 have similar clinical symptoms and pathogenicity and cause death in 75% of ducks on days 3-6 after infection. Key Words: H5N1 Virus, Clade 2.3.2, Clade 2.1.3, Phylogenetic Tree, Pathogenecity